Cardiovascular magnetic resonance findings in non‐hospitalized paediatric patients after recovery from COVID‐19. (27th October 2021) - Seidel, Franziska; Kuehne, Titus; Kelle, Sebastian; Doeblin, Patrick; Zieschang, Victoria; Tschoepe, Carsten; Al‐Wakeel‐Marquard, Nadya; Nordmeyer, Sarah
Abstract: Aims: Our study aimed to investigate the cardiac involvement with sensitive tissue characterization in non‐hospitalized children with coronavirus disease 2019 (COVID‐19) infection using cardiovascular magnetic resonance (CMR) imaging. Methods and results: We prospectively enrolled children who recovered from mildly symptomatic COVID‐19 infection between November 2020 and January 2021. Patients underwent CMR at 1.5 T (Achieva, Philips Healthcare, Best, the Netherlands) including cine images, native T1 and T2 mapping. Healthy children and paediatric patients with biopsy‐proven myocarditis served as control groups. We performed CMR in 18 children with a median (25th–75th percentile) age of 12 (10–15) years, 38 (24–47) days after positive PCR test, and compared them with 7 healthy controls [15 (10–19) years] and 9 patients with myocarditis [10 (4–16) years]. The COVID‐19 patients reported no cardiac symptoms. None of the COVID‐19 patients showed CMR findings consistent with a myocarditis. Three patients (17%) from the COVID‐19 cohort presented with minimal pericardial effusion. CMR parameters of COVID‐19 patients, including volumetric and strain values as well as T1 and T2 times, were not significantly different from healthy controls, but from myocarditis patients. These had significantly reduced left ventricular (LV) ejection fraction ( P  = 0.035), LV global longitudinal strain, and left atrial strain values as well as elevated native T1 values compared with COVID‐19 patients ( P  < 0.001, respectively). Conclusions: There was no evidence of myocardial inflammation, fibrosis, or functional cardiac impairment in the studied cohort of children recently. CMR findings were comparable with those of healthy controls. Pericardial effusion suggests a mild pericarditis in a small subgroup. This is pointing to a minor clinical relevance of myocardial involvement in children after mildly symptomatic COVID‐19 infections.